قياس وتحليل تأثير تقلبات سعر البترول في استجابة السياسة المالية في الجزائر دراسة قياسية للفترة 2000 - 2021 باستخدام نم وذج NARDL - رحالي بلقاسم,; بوعافية سمير, (Journal of North African Economies, 2025)
This study aims to measure and analyze the asymmetry in the impact associated with crude oil price shocks on the fiscal policy response in Algeria during the period 2000-2021, Using The Non Linear Autoregressive Distributed Lag Model (NARDL), coupled with asymmetry test and shock analysis. The econometrics results showed that there are: firstly, along-term equilibrium relation ship between government spending and positive changes in the price of oil and negative changes in the price of oil. Secondly, the price of crude oil exerts an asymmetric effect on government spending in the short and long term. Thirdly, Fiscal policy in Algeriais more responsive to positive shocks in the price of crude oil in the short and long terms, compared to negative shocks in the price of crude oil.